Schooling, Interrupted - Jennifer Thompson; Sarah Fraser; Isabelle Archambault; Nancy Beauregard; Véronique Dupéré; Katherine Frohlich (Journal of Teaching and Learning, 2021)
Among the concerns about youth wellbeing during the COVID-19 pandemic, one well-documented impact is youth motivation, particularly in relation to schooling. Yet many questions remain: How are youth experiencing motivation? What factors affect their motivation? How are youth differentially experiencing motivation? This article addresses young people’s experiences of motivation during the first wave of the pandemic as explored through participatory visual research. In Spring 2020, the Quebec private and public secondary school systems responded very differently to school closures. Private schools pivoted to distance learning within about two weeks, whereas public schools took almost two months to provide formal instruction. Bringing youth’s accounts of motivation into conversation with youth’s concerns about the inequities across the private and public school systems offers a rich opportunity to revisit Self-Determination Theory as an established theory of motivation. Youth’s analyses urge us to revisit the conceptualization of “structure” within this theory and how structure might offer a junction for accounting for more macrostructural inequalities within motivation research.